Are subsidies for thermally-driven solar-assisted cooling systems consistent? A critical investigation for Southern Italy. (November 2022) - Marletta, L.; Evola, G.; Arena, R.; Gagliano, A.
Abstract: The growing availability of low-cost electricity-driven air-conditioning systems has determined a huge increase in the electricity demand for space cooling, especially in warm and hot climates. In this framework, thermally-driven solar-assisted cooling systems are a very interesting alternative, since they are mainly fed by converting the largely available solar radiation into thermal energy: however, their economic convenience is still questionable. For this reason, many EU states have introduced suitable subsidies: in Italy, the so-called "Conto Termico" proposes cash-back incentives proportional to the thermal energy delivered by the solar field. This study investigates the suitability and consistency of these subsidies, by considering a case study including a thermally-driven solar-assisted absorption chiller that cools down an office building located in Palermo (Southern Italy). The study looks into the sizing of the system and evaluates its techno-economic feasibility by considering the incentives introduced by the Italian "Conto Termico". The results highlight that the proposed solar-assisted absorption cooling system can reduce primary energy demand and CO2 emissions by around 75% if compared to a conventional electric chiller, under a reasonable sizing of the solar section. The subsidies are proportional to the thermal energy delivered by the solar collectors, and thus tend to favour the adoption of high collecting surfaces: for instance, installing 2 m 2 of evacuated tube solar collectors per unit cooling capacity ensures relatively low payback periods of 15 years or even less. However, the energy performance of the system does not improve accordingly with higher collecting surfaces, since a non-negligible rate of delivered thermal energy is wasted, as witnessed by the decreasing seasonal COP. Moreover, Flat Plate Collectors are improperly penalized, and the real local operating conditions are not considered in the calculation. This suggests that the rationale leading Italian subsidies are not consistent, and needs being improved. Highlights: The paper studies the energy and financial performance of a solar-assisted absorption cooling system in Southern Italy. The primary energy demand drops by 75% if compared to a conventional electric chiller. A solar surface of at least 2 m 2 per unit cooling capacity is needed. Italian subsidies can ensure payback periods below 15 years. Subsidies tend to favour high collecting surface, irrespective of the actual energy performance.